PENGELOLAAN MANAJEMEN RESIKO GADAI NON-EMAS TIDAK TERTEBUS DI PEGADAIAN SYARIAH CABANG BLAURAN - Dyah Palupi Dwi Cahyani; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study is aimed to know the mechanism of risk management in the management of unredeemed non-gold pawn in Blauran Sharia Pawnshop. Through the three phases of risk management that is risk identification, risk ranking, and risk control Blauran Sharia Pawnshop expected can be more minimize the risks, one of them is unredeemed non-gold pawn. The research method used was qualitative. Research data is obtained by doing interview techniques and documentation to the informant that was assistant deputy manager Pawnshop of Surabaya Regional Office, Head of Blauran Surabaya Sharia Pawnshop branch, and staff of Blauran Surabaya Sharia Pawnshop. The research showed that Blauran Sharia Pawnshop has run the risk management process in three ways: risk identification, risk ranking based on potency and the most influential risk, and risk control by conducting auction on non-goldpawning items that were not redeemed.Keyword: Risk Management, sharia mortgage, sharia pawnshop,unreedemed non-gold pawnREFERENCES Djohanputro, Bramantyo. 2006. Manajemen Resiko Korporat Terintegrasi. Jakarta: PPMHasan, M. Ali. 2004. Berbagai Macam Transaksi dalam Islam. Jakarta: PT. Raja Grafindo PersadaHendi, Suhendi. 2011. Fiqh Muamalah. Jakarta: Rajawali Pers.Karim, A. Adhiwarman. 2001. Ekonomi Islam. Jakarta: PT. Gema Insani.Kasmir. 2002. Bank dan Lembaga Keuangan Lainnya. Jakarta: PT. Raja Grafindo Persada.Susilo, J dkk. 2010. Manajemen Resiko Berbasis ISO 31.000: Untuk Industri Non-Perbankan. Jakarta: PPM Manajemen.Syafe’i, Rachmat. 2001. Fiqih Muamalah. Bandung: Pustaka SetiaTampubolon, Robert. 2006. Manajemen Resiko: Pendekatan Kualitatif Untuk Bank Komersial. Jakarta: PT.Elex Media Komputindo.Yin, Robert K. 2009. Studi Kasus(Desain dan Metode). Diterjemahkan oleh Drs. M. Djauzi Mudzakir, MA. Jakarta: PT. Raja Grafindo Persada.